Change in mutation frequency at a TP53 hotspot during culture of ENU-mutagenised human lymphoblastoid cells. (10th July 2019) - Watanabe, Masahiko; Toudou, Masae; Uchida, Taeko; Yoshikawa, Misato; Aso, Hiroaki; Suemaru, Katsuya
Abstract: Mutations in oncogenes or tumour suppressor genes cause increases in cell growth capacity. In some cases, fully malignant cancer cells develop after additional mutations occur in initially mutated cells. In such instances, the risk of cancer would increase in response to growth of these initially mutated cells. To ascertain whether such a situation might occur in cultured cells, three independent cultures of human lymphoblastoid GM00130 cells were treated with N -ethyl- N -nitrosourea to induce mutations, and the cells were maintained for 12 weeks. Mutant frequencies and spectra of the cells at the Msp I and Hae III restriction sites located at codons 247–250 of the TP53 gene were examined. Mutant frequencies at both sites in the gene exhibited a declining trend during cell culture and reached background levels after 12 weeks; this was also supported by mutation spectra findings. These results indicate that the mutations detected under our assay conditions are disadvantageous to cell growth.